Antioxidant Activity Test of Black Rice (Oryza sativa L. Indica) Extract and Total Phenolic Test of Soybean Sprout (Glycine max L.) Extract Using 70%, 90%, and 96% Ethanol Variations. - Rizlah Maulizah; Kintoko; Nina Salamah; Elfi Anis Saati (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: The human body requires external antioxidants to neutralize free radicals that cause cellular damage and degenerative diseases. Black rice contains higher anthocyanin levels than red rice, while soybean germination increases flavonoids, phenolic compounds, and secondary metabolites.Objective: This study aimed to determine the total phenolic content of germinated soybeans extracted using three ethanol solvent concentrations (70%, 90%, and 96%) and to valuate the antioxidant activity of soybean and black rice extracts as copigmentation agents. Methods: Soybean extracts were obtained by maceration using different ethanol concentrations, followed by analysis of total phenolic content and antioxidant activity. Black rice extract was evaluated for antioxidant activity using the DPPH method to obtain a stable antioxidant with a very strong IC₅₀ value. Results: The total phenolic content of germinated soybean extracts varied with solvent concentration: ethanol 70% yielded 2.24 mg GAE/g, ethanol 90% yielded 7.14 mg GAE/g, and ethanol 96% yielded 3.36 mg GAE/g. The total anthocyanin content of black rice extract determined by the pH differential method was 8.182 mg/100 g, with an antioxidant activity IC₅₀ of 82.24 ± 3.6 ppm, categorized as strong. The IC₅₀ value of the non-copigmented sample was 83.71 ± 1.6 ppm (moderate), while copigmentation ratios of 1:1, 1:2, and 1:3 resulted in IC₅₀ values of 70.83 ± 0.8 ppm (strong), 62.97 ± 1.2 ppm (strong), and 38.53 ± 0.3 ppm (very strong), respectively. Conclusion: Extraction of germinated soybeans using ethanol 90% significantly increased total phenolic content (p < 0.05). Copigmentation of black rice anthocyanin flavylium with germinated soybean polyphenols at a 1:3 ratio produced very strong antioxidant activity (p < 0.05), indicating its potential as a copigmentation agent in functional food products.